A compact ultra wideband antenna with WiMax band rejection for energy scavenging - Jalil Y.E.; Kasi B.; Chakrabarty C.K. (Institute of Physics Publishing, 2023)
Radio Frequency (RF) energy harvesting has been rapidly advancing as a promising alternative to existing energy scavenging system. A well designed broadband antenna such as ultra-wideband (UWB) antenna can be used as one of the major components in an RF energy scavenging system. This paper presents a compact UWB antenna showing good impedance matching over a bandwidth of 2.8 to 11 GHz, suiTable for broadband RF energy scavenging. Nevertheless, the antenna usage in wireless communication has a limitation due to the problem of interference between UWB system and other narrowband systems. Thus, the proposed antenna is successfully designed with a single band-notched at the targeted WiMAX operating band of 3.3 to 3.6 GHz. Published under licence by IOP Publishing Ltd.